CRAN-34. TRANSCRIPTOMIC AND PROTEOMIC COMPARISON OF PEDIATRIC AND ADULT ADAMANTINOMATOUS CRANIOPHARYNGIOMA. Issue 2 (22nd June 2018) - Prince, Eric; Whelan, Ros; Donson, Andrew; Staulcup, Susan; Lillehei, Kevin; Foreman, Nicholas; Massimi, Luca; Handler, Michael; Hankinson, Todd
Abstract: Adamantinomatous craniopharyngioma (ACP) is a biologically benign but clinically aggressive lesion that has a significant impact on quality of life. The incidence of the disease has a bimodal distribution with peaks occurring in children and adults. Our group previously published the results of a transcriptome analysis of pediatric ACPs that identified several genes that were consistently overexpressed relative to other brain tumors. We now present the results of a transcriptome analysis of both pediatric and adult ACP to identify biological differences between these groups that may provide novel therapeutic insights, or support the assertion that potential therapies identified through the study of pediatric ACP may also have a role in adult ACP. Following bulk RNA sequencing, we explored the differential expression of adult ACP versus pediatric ACPs via geneset enrichment analysis. Preliminary studies identified a decreased cytokine gene expression profile in adult ACP that may correspond to a reduced senescence-associated secretory phenotype (SASP), which has recently been described in pediatric ACP. Additionally, our results corroborate our previous work demonstrating an increase in IL-6 expression and overall inflammatory response in pediatric tumors. To further characterize age-associated transcriptomic differences, we performed immunohistochemistry, immunoblotting, and other proteomic studies. Our results demonstrate phenotypic similarities and differences between pediatric and adult ACP.